2020
DOI: 10.1111/eci.13456
|View full text |Cite
|
Sign up to set email alerts
|

The impact of volume substitution on post‐operative atrial fibrillation

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Pain, especially unrelieved pain, could be a trigger for atrial fibrillation. However, in a placebo-controlled clinical trial, Dexmedetomidine for reduction of atrial fibrillation and delirium after cardiac surgery (DECADE), the levels of pain and opioid consumption was unremarkable between patients who developed atrial fibrillation post-operation versus patients who did not [ 20 ]. Because of the multifactorial nature of atrial fibrillation and delirium, the findings from this study suggest no association between opioid use and atrial fibrillation and delirium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain, especially unrelieved pain, could be a trigger for atrial fibrillation. However, in a placebo-controlled clinical trial, Dexmedetomidine for reduction of atrial fibrillation and delirium after cardiac surgery (DECADE), the levels of pain and opioid consumption was unremarkable between patients who developed atrial fibrillation post-operation versus patients who did not [ 20 ]. Because of the multifactorial nature of atrial fibrillation and delirium, the findings from this study suggest no association between opioid use and atrial fibrillation and delirium.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study 43% of patients developed POAF and showed increased post-operative fluid balance and M-terminal pro-brain natriuretic peptide (NT-ProBNP). Also, anemia pre-operation led to increased transfusion volumes, and suggests that POAF may be triggered by global cardiac strain [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…(3,10,21) It seems, that not only intraoperative blood loss per se but also the subsequent intra-and postoperative red blood cell or platelet transfusion fosters POAF development. (22) Stretch of myocardial tissue by subsequent volume load enhances cardiac strain as a stressor for POAF.…”
Section: Inflammation Cardiac Strain and Postoperative Atrial Fibrillationmentioning
confidence: 99%
“…3,10,21 It seems that not only intraoperative blood loss per se but also the subsequent intra-and postoperative red blood cell or platelet transfusion fosters POAF development. 22 Stretch of myocardial tissue by subsequent volume load enhances cardiac strain as a stressor for POAF. Assuming the mentioned multifactorial approach, in line with a potential impact on cardiac strain, patients with higher preoperative GDF-15 levels experienced nearly 1.5 times more often POAF.…”
Section: Inflammation Cardiac Strain and Postoperative Atrial Fibrillationmentioning
confidence: 99%
“…Furthermore, invasive electrophysiological examination after cardiac surgery is time‐consuming and potentially harmful in the early post‐operative phase and, thus, not feasible in daily practice. Several factors have been identified to increase the risk of NOAF: (i) vasoactive agents used for haemodynamic stabilization, 5,8 (ii) poor post‐operative pain control, 9 and (iii) post‐operative fluid overload 10,11 . Additional factors contribute to the local myocardial inflammation due to reperfusion injury after cardiopulmonary bypass 12 .…”
Section: Introductionmentioning
confidence: 99%